Hydrogeochemical Evolution Along Groundwater Flow Paths in the Manas River Basin, Northwest China. Issue 4 (15th October 2018) - Wang, Jianjun; Liang, Xing; Liu, Yanfeng; Jin, Menggui; Knappett, Peter S.K.; Liu, Yalei
Abstract: The impacts of long‐term pumping on groundwater chemistry remain unclear in the Manas River Basin, Northwest China. In this study, major ions within five surface water and 105 groundwater samples were analyzed to identify hydrogeochemical processes affecting groundwater composition and evolution along the regional‐scale groundwater flow paths using the multivariate techniques of hierarchical cluster analysis (HCA) and principal components analysis (PCA) and traditional graphical methods for analyzing groundwater geochemistry. HCA classified the groundwater samples into four clusters (C1 to C4). PCA reduced the dimensionality of geochemical data into three PCs, which explained 86% of the total variance. The results of HCA and PCA were used to identify three zones: "recharge, " "transition, " and "discharge." In the recharge zone the groundwater type is Ca‐HCO3 ‐SO4 and is primarily impacted by the dissolution of calcite and silicate weathering. In the transition zone the groundwater type is Ca‐HCO3 ‐SO4 ‐Cl and is impacted by rock dissolution and reverse ion exchange. In the discharge zone the groundwater type is Na‐Cl and is impacted by evaporation and reverse ion exchange. In addition, anthropogenic activities impact the groundwater chemistry in the study area. The groundwater type generally changes from Ca‐HCO3 ‐SO4 in the recharge area to Na‐Cl in the discharge area along the regional‐scale groundwater flow paths. This study provides a process‐based knowledge for understanding the interaction of groundwater flow patterns and geochemical evolution within the Manas River Basin. Abstract : Article impact statement : Hydrogeochemical evolution along the groundwater flow paths was analyzed by using multivariate statistics and graphical methods.